A study on relationship between electronic banking and liquidity management on Iranian banks - Hassan Ghodrati; Masoumeh Soleimani khah (Management Science Letters)
E-banking has been extensively developed in recent decades and most banks need to have such services in their daily activities. Therefore, it is necessary that banks do a better management on banks’ liquidity risks. Electronic banking and the expansion of its scale from POSs and ATMs to telephone banking, mobile banking and internet banking have increased banking transactions, significantly. The purpose of this investigation is to evaluate the relationship between the development of e-banking and liquidity management using liquidity ratios. The focus of this investigation has been on the amounts of transaction of ATM machines, POSs and PIN PADs as the most important means of electronic banking. In this respect, the data obtained from 14 private and public bank representatives of banking system over the period 2007-2012 are considered. Our survey indicates that the characteristics of electronic banking significantly influence on liquidity.